PENERAPAN, PENGELOLAAN, DAN PERTANGGUNG-JAWABAN ATAS BENDA SITAAN DAN BARANG RAMPASAN NEGARA DI RUMAH PENYIMPANAN BENDA SITAAN NEGARA (RUPBASAN JAMBI) - Kevin Pramadani; R. Rahaditya (Jurnal Hukum Adigama, 2022)
In May 2019, three civil servants from the Jambi Kumham Regional Of ice were arrested for stealing11 cellphones at the State Property Confiscated Objects Storage (RUPBASAN) of ice. RUPBASANshould be a safe place for confiscated, but with the theft case in RUPBASAN, it is certainly interestingto examine juridically regarding the cause of the case, legal protection for confiscated goods,obstacles experienced by RUPBASAN and handling ef orts. Referring to these problems, the authoruses empirical juridical research methods. Based on the results of the study when referring to thetheory of law enforcement according to Friedman, namely structure, substance and culture, then in thiscase the structure and substance of the law have actually been formed, the lack of a sense ofresponsibility to keep objects from being lost, dishonesty and abuse of power for selfish purposesshows the culture that exists within the implementing of icers that causes such cases to occur. Theobstacles experienced by the Jambi RUPBASAN are Internal Constraints and External Constraints.Ef orts to resolve these obstacles are by strengthening coordination and synchronization.Strengthening coordination between the Government, the Ministry of Law and Human Rights, theIndonesian National Police, RUPBASAN, and parties related to the management of confiscated objectsand state confiscations, so that internal problems can be resolved. Synchronization of work guidelines,management regulations and regulations for implementing cooperation in the management ofconfiscated objects and state confiscations, so that in the process of implementing the management ofconfiscated objects and state confiscated goods.